Criteria for assessing children’s abilities when selecting them for hockey - Istomin, S.O.; Polozov, A.A.; Murza, A.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and test a set of criteria for assessing children’s abilities, supplementing existing standards to improve the effectiveness of individual selection at the initial stage of training. Methods and structure of the study. The work used questionnaires, anthropometric measurements, testing of general and special physical fitness, functional testing, analysis of neurodynamic parameters, pedagogical observation and processing of statistics of gaming activity. The study included 120 8-year-old children who were trained at the sports school of the Olympic reserve "Spartakovets" in 2021-2024. Results and conclusions. The use of the proposed criteria increased the percentage of transfer to the next stage from 71.5% to 97.9%, and the assignment of sports grades to 93.6%. The practical significance of the work lies in increasing the objectivity and accuracy of the selection, ensuring the individualization of training and the formation of an optimal trajectory for the development of young hockey players. The developed criteria base for identifying the abilities of 8-year-olds in the sport of hockey, complementing the system of physical fitness standards of the Federal Standard, makes it possible to increase the effectiveness of the individual selection procedure at the initial stage of sports training.